From Hegel to Marx : - Hook, Sidney (The University of Michigan Press, 1962)
In this brilliant work, first published in 1936, Sydney Hook seeks to resolve one of the classic problems of European intellectual history: how the political radicalism and philosophical materialism of Karl Marx issued from the mystical and conservative intellectual system of G.W.F. Hegel.